A systematic method to evaluate newborn weight loss and its influence on breastfeeding success - Catarina Schrempp-; Maria C. Soares-Ma; José P. Pereira; Ana Rodrigues; Ana C. Feijó-S (Publicaciones Permanyer, 2024)
Introduction and objectives: Increasing evidence shows that newborn weight loss is significantly influenced by the type of labour among other factors, implying a wider understanding of weight loss and its context to intervene accordingly. Given the importance of breastfeeding and the impact of infant formula use on its success, we aimed to understand the impact of the application of nomogram weight loss tools in initiating infant formula. Methods: This study included 206 newborns in a nonrandomised clinical trial, who were divided into two groups. In the intervention group, weight loss was managed through the use of the "Early Weight Loss Nomogram", rather than with clinical experience associated with weight loss percentage, the standard type of care. We analysed the characteristics of mothers, newborns, and labours and their influence on each group. Results: We found that the introduction of formula milk due to weight loss tended to diminish (61.3% vs. 38.7%, p = 0.082) and nurses' suggestions dropped to zero in the intervention group. The intervention group reported a longer period of exclusive breastfeeding, up to nearly six months of age. The babies who were not breastfed during the first hour of life were more often supplemented (78.6% vs. 21.4%, p < 0.001) and those with skin-on-skin contact were given a lower proportion of formula milk (69.8% vs. 30.2%, p < 0.001). Discussion: Application of the nomogram allowed the introduction of formula milk in more selected cases. This tool should be applied in healthcare units because it increases health professionals' awareness of the criteria for formula supplementation.